Drivers of climate change in selected emerging countries: the ecological effects of monetary restrictions and expansions - Thanh Phuc Nguyen; Tho Ngoc Tran; Thi Thu Hong Dinh; Tri M. Hoang; Trang Duong Thi Thuy (Cogent Economics & Finance, 2022)
Drivers of environmental quality have recently been identified in a large body of literature. However, the ecological effects of both regimes of monetary policy remain under-explored so far. Moreover, previous studies use limited samples and econometric approaches. Climate change from the empirical perspective of the country's monetary policy has recently become a promising avenue to investigate. Motivated by the aforementioned research gaps and increasing attention from energy researchers and policy-makers, this research aims to test the monetary restrictions and expansion on climate change represented by CO2 emissions, after controlling other significant drivers. We use a dataset from 1998 to 2018 for a sample of 14 selected emerging economies and quantitatively advanced techniques for panel data analysis, such as Ordinary Least Squares (OLS), Dynamic OLS, Fully-Modified OLS, and Panel Quantile Regression. We also use a two-step system generalized method of moments to avoid concerns about endogeneity and heteroskedasticity issues. We find strong evidence that contractionary and expansionary monetary policy both eliminate and escalate the environmental degradation through an increase in CO2 emissions, respectively. Moreover, these ecological effects of monetary policy interestingly appear in the middle and large quantiles of CO2 levels. Based on these findings, the research offers some key implications for policymakers looking to initiate green monetary policy for carbon abatement.
Keywords: F14; F15; F43; E31; Q41; Q43; 330; Monetary policy; climate change; emerging countries; dynamic OLS; fullymodified OLS; panel quantile regression